Strong metal-oxygen interaction in uracils. X-ray crystal structure of bis-(1,3-dimethyluracil)dichlorocopper(II). - Cartwright, B A (1978)
An X-ray structure determination showed that in the compound bis-(1,3-dimethyluracil)-dichlorocopper(II) the uracil moiety is strongly bonded to the metal via the O(4) atom. Changes in the i.r. spectra on metal binding are discussed. Details of the structural parameters have been deposited as Supplementary Publications SUP 50091 (3 pages) at the British Library Lending Division, Boston Spa, Wetherby, West Yorkshire LS23 7BQ, U.K., from whom copies can be obtained on the terms indicated in Biochem. J. (1978) 169, 5.